Ekspresi dan Peran Siklooksigenase-2 dalam Berbagai Penyakit di Rongga Mulut - Prasetya, Rendra Chriestedy (STOMATOGNATIC- Jurnal Kedokteran Gigi, 2015)
AbstractBackground: Cyclooxygenase - 2 is part of the cyclooxygenase enzyme thatplays a role in the inflammatory process has produce of prostaglandins (PG) such asPGE2. Prostaglandin E2 plays an important role in the pathogenesis of periodontaldisease because it leads to increased vascular permeability, vasodilatory, edema.Objective: This review intends to give an overview the role of COX-2 in oral diseaseslikely periodontitis to be better understood and the future of our research that mayfacilitate the development of diagnosis and therapies. Literature review:Cyclooxygenase is enzyme that play of catalyze biosynthesis of prostaglandins andcontained in two forms of COX-1 and COX-2. Cyclooxygenase-2 activity has increasedin inflammation especially wound formation and periodontitis. In periodontitis, invasionof lipopolysacharide can Increase COX-2 activity in smooth blood muscle that can leadatherosclerosis. COX-2 inhibition can lead healing process that characterizedfibroblast formation.Conclusion : the presence COX-2 in gingival tissue and gingivalcrevicular fluid can be used as biomarkers about the severity of periodontal disease,healing process and risk of atherosclerosis.Key word : Cyclooxygenase-2, Periodontitis, wound healing, atherosclerosis